Generasi Alpha: Sebuah Pola Pendekatan Guru Pendidikan Agama Kristen Dalam Melakukan Pendidikan Karakter, Moral dan Kerohanian Peserta Didik - Sugeng Prayitno; Pasaribu, Ferdinan (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2023)
The alpha generation is a generation born surrounded by technological progress. It will have a very bad and negative impact if it is not balanced with children's character and spiritual education from an early age, because it will have an impact on the child's individual growth as well as motoric and emotional growth that is not optimal. Children's character and spiritual education must start from the family and be carried out by parents. This research uses a literature study method by utilizing various kinds of literature related to the research theme. The aim of this research is to provide a pattern that parents can use in carrying out character and spiritual education in alpha generation children. The results of this research are that character and spiritual education patterns can be carried out by cultivating character and spirituality, providing mentoring, and habituation. The conclusion of this research is the importance of a pattern of approach in carrying out character and spiritual education for children in the alpha generation, a generation that is familiar with the world of technology and its consequences.